Advanced coronary and carotid arteriopathy in young adults with childhood-onset chronic renal failure - Oh, Jun; Wunsch, Rainer; Turzer, Martin; Bahner, Malte Leonardo; Raggi, Paolo; Querfeld, Uwe; Mehls, Otto; Schaefer, Franz (Circulation, 2002)
Cardiovascular mortality is excessive in young adults with end-stage renal disease (ESRD). The factors contributing to ESRD-related vascular disease are incompletely understood. Young adults with childhood-onset chronic renal failure (CRF) are uniquely suited for risk factor assessment because of their long-term exposure at an age when vascular pathology in the general population is still minimal.
Gesehen am 11.12.2020